Recent Study Shows the Effects of Roadways on Vehicle Performance - Kogler, Bob (2025)
Most considerations regarding fuel consumption and the rate of pollutant emissions are typically based on estimated vehicle fleet size, average speed, and distance traveled within a given area. However, a recently completed study indicated that road gradients and curves, pavement condition, and speed variations are equally significant factors.